Relationship of Depression and Sleep Quality among North Jakarta Medical Students during the COVID-19 Pandemic - Annabella Naida Tanusetiawan; Surilena Surilena; Nelly Tina Widjaja; Dharmady Agus (Fakultas Kedokteran Universitas Brawijaya, 2022)
Medical students with high academic load have had elevated baseline rates of depression and poor sleep quality. During the COVID-19 pandemic, medical students are more susceptible to depression and poor sleep quality. This study aimed to analyze depression and sleep quality among medical students at the School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia (FKIK UAJ) during the COVID-19 pandemic. A cross-sectional study was conducted among pre-clinical and clinical students of FKIK UAJ academic year 2020/2021. Respondents were selected through proportional systematic random sampling to fulfill the Patient Health Questionnaire-9 (PHQ-9) and Pittsburgh Sleep Quality Index (PSQI) for depression and sleep quality. The data were analyzed using Mann Whitney U-Test. There were 63.3% of 635 respondents with depression, in which 39.4% respondents had mild depression, 14.2% respondents with moderate depression, and 9.8% respondents with severe depression. There were 59,2% of respondents with poor sleep quality. Depression was highest in females (67.2%) and pre-clinical stage of 2020 intake year (74.6%), and among clinical level students of 2018 (56%) and 2019 (53.9%) intake year. Poor sleep quality was also highest in females (62.8%) and pre-clinical 2020 intake year (69.8%), and among clinical level students of 2018 (53%) and 2019 (51.9%) intake year. The Mann-Whitney U-test showed a significant difference between depression level and sleep quality in pre-clinical and clinical students of FKIK UAJ during the COVID-19 pandemic (p value=0.000). Depression and sleep quality among medical students of FKIK UAJ during the COVID-19 pandemic were significantly associated.